Molecular Biomarkers Predictive of Sertraline Treatment Response in Young Children With Autism Spectrum Disorder - Alolaby, Reem Rafik; Jiraanont, Poonnada; Durbin-Johnson, Blythe; Jasoliya, Mittal; Tang, Hiu-Tung; Hagerman, Randi; Tassone, Flora (Frontiers in Genetics, 2020)
Sertraline is one among several selective serotonin reuptake inhibitors (SSRIs) that sometimes can exhibit improvement of language development in Autistic Spectrum Disorder (ASD); however, the molecular mechanism has not been elucidated. A double blind, randomized, placebo-controlled 6-month clinical trial of low-dose sertraline in children ages 39-71 months old with ASD was conducted at the UC Davis MIND Institute to evaluate the efficacy and benefit with respect to early expressive language development and global clinical improvement. This study also aimed to identify molecular biomarkers that may by playing an important role in the serotonin pathway and might be predictive of a clinical response to sertraline. Fifty eight subjects (3-6 years) with the diagnosis of ASD were randomized to sertraline or placebo. Eight subjects from the sertraline arm and five from the placebo arm discontinued from the study. Furthermore, 4 subjects did not have a successful blood draw. Hence, genotypes for 41 subjects (20 on placebo and 21 on sertraline) were determined for several genes involved in the serotonin pathway including the serotonin transporter-linked polymorphic region (5-HTTLPR), the tryptophan hydroxylase 2 (TPH2), and the Brain-Derived Neurotrophic Factor (BDNF). In addition, plasma levels of BDNF, Matrix metallopeptidase 9 (MMP9) and a selected panel of cytokines were determined at baseline and post-treatment. Intent-to-treat analysis revealed several primary significant correlations between molecular changes and the Mullen Scales of Early Learning (MSEL) and Clinical Global Impression Scale – Improvement (CGI-I) of treatment and control groups but they were not significant after adjustment for multiple testing. Sertraline showed no benefit for treatment of young children with ASD in language development or changes in molecular markers in this randomized 6 month-controlled trial. These results indicate that sertraline may not be beneficial for the treatment of children with ASD; however, further investigation of larger groups as well as longer term follow-up studies are warranted.